Ultrathin V2O5 nanosheet cathodes : realizing ultrafast reversible lithium storage - Rui, Xianhong (2013)
Few-layer V2O5 nanosheets with a thickness of 2.1–3.8 nm have been successfully synthesized in this work via a simple and scalable liquid exfoliation technique. The unique nanostructure allows the high-rate transportation of lithium ions and electrons due to very short diffusion paths provided by this ultrathin thickness, resulting in Li-ion cathodes with remarkable energy and power densities.